2019
DOI: 10.1212/nxg.0000000000000378
|View full text |Cite
|
Sign up to set email alerts
|

Critical exon indexing improves clinical interpretation of copy number variants in neurodevelopmental disorders

Abstract: ObjectiveTo evaluate a new tool to aid interpretation of copy number variants (CNVs) in individuals with neurodevelopmental disabilities.MethodsCritical exon indexing (CEI) was used to identify genes with critical exons (CEGs) from clinically reported CNVs, which may contribute to neurodevelopmental disorders (NDDs). The 742 pathogenic CNVs and 1,363 variants of unknown significance (VUS) identified by chromosomal microarray analysis in 5,487 individuals with NDDs were subjected to CEI to identify CEGs. CEGs i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 41 publications
0
5
0
Order By: Relevance
“…Analyses using the “critical-exon” method ( Uddin et al, 2014 , 2016 ) to identify constraint candidate genes discerned a high number of CEGs within the pathogenic variants (7.5) compared to VOUS (0.19) ( p = 0.0002). Moreover, CEGs per pathogenic CNV were also previously reported ( Wassman et al, 2019 ) as reflective of length bias and gene density of pathogenic variants. From the previous studies ( Uddin et al, 2014 ; Uddin et al, 2016 ; Wassman et al, 2019 ), it is observed that critical exon genes are significantly enriched for de novo mutations in autism probands but not in unaffected siblings or in population control subjects.…”
Section: Discussionmentioning
confidence: 73%
See 2 more Smart Citations
“…Analyses using the “critical-exon” method ( Uddin et al, 2014 , 2016 ) to identify constraint candidate genes discerned a high number of CEGs within the pathogenic variants (7.5) compared to VOUS (0.19) ( p = 0.0002). Moreover, CEGs per pathogenic CNV were also previously reported ( Wassman et al, 2019 ) as reflective of length bias and gene density of pathogenic variants. From the previous studies ( Uddin et al, 2014 ; Uddin et al, 2016 ; Wassman et al, 2019 ), it is observed that critical exon genes are significantly enriched for de novo mutations in autism probands but not in unaffected siblings or in population control subjects.…”
Section: Discussionmentioning
confidence: 73%
“…Moreover, CEGs per pathogenic CNV were also previously reported ( Wassman et al, 2019 ) as reflective of length bias and gene density of pathogenic variants. From the previous studies ( Uddin et al, 2014 ; Uddin et al, 2016 ; Wassman et al, 2019 ), it is observed that critical exon genes are significantly enriched for de novo mutations in autism probands but not in unaffected siblings or in population control subjects. Identifying critical exon genes has shown ( Wassman et al, 2019 ; Safizadeh Shabestari et al, 2022 ) improvement in clinical interpretations of rare CNVs.…”
Section: Discussionmentioning
confidence: 73%
See 1 more Smart Citation
“…As outlined in Figure 1 , 2037 neurodevelopmental genes [ 29 ] which have links to neurological and developmental abnormalities were included in the dataset. Along with these neurodevelopmental genes, the 594 genes found in the CNVs from clinical subjects were included as the initial dataset (Total = 2631 genes).…”
Section: Methodsmentioning
confidence: 99%
“…The syndromic cases are often considered to harbor larger genetic defects including copy number variants, whereas nonsyndromic forms are often due to monogenic causes. 5,6 Chromosomal abnormalities are found in around 25% of cases and monogenic causes in up to 10% of cases with developmental disabilities. 1,7,8 Due to widespread availability and increased knowledge of treating physicians after instituting such guidelines, several novel neurodevelopmental disorders have been discovered in recent years.…”
Section: Introductionmentioning
confidence: 99%